Motivating employees - reaseach at the north Petro Vietnam fertilizer and chemicals Joint stock Company : Luận văn ThS. Quản lý công (Chương trình đào tạo thí điểm) - Trần Thanh Bình (H.: ĐHKT, 2018)
59 p.